(untitled) (International Journal of Applied Research in Management and Economics, 2018)
This study evaluates the effect of customers’ deposits on loan administration in Nigerian banks from 2007 to 2016. Secondary data were obtained from annual reports accounts of ten (10) quoted Nigerian commercial Banks. The variables for which data were sourced include Loans and advances, Customers’ deposits, Investment, Interest Income, and Operating expenses from 2006 to 2015. Panel data results show that customers’ deposits has positive significant impact on loan and advances of the sampled banks (t= 4.60 and P>|t = 0.000 < 0.05) Also, investment has positive significant effect on loan and advances (t value 2.68 and P>|t = 0.009 < 0.05). More so, there is a positive significant effect of interest income on loan and advances (t value 4.74 and P>|t = 0.000 < 0.05), which is gain or returns from the investment by the sampled banks enhanced positive impact on loan administration in Nigeria banks. In contrary, operating expenses has a negative insignificant effect of on loan and advances (t value – 0.74 and P>|t = 0.460 > 0.05). In conclusion, customers’ deposits have a strong, statistical and significant positive impact on loans and advances in Banking Sectors in Nigeria. To enormously improve customers’ deposits, the bank should design more packages that would entice and motivate customers’ patronage and deposits, this will invariably increase customers’ loyal to deposit more cash with the bank which will ultimately generate additional revenue for banks to satisfying their customer in terms of loan and advances.